Efficient enzymatic synthesis of l-rhamnulose and l-fuculose. Issue 3 (1st February 2016) - Wen, Liuqing; Zang, Lanlan; Huang, Kenneth; Li, Shanshan; Wang, Runling; Wang, Peng George
Graphical abstract: Abstract: l -Rhamnulose (6-deoxy-l - arabino -2-hexulose) andl -fuculose (6-deoxy-l - lyxo -2-hexulose) were prepared froml -rhamnose andl -fucose by a two-step strategy. In the first reaction step, isomerization ofl -rhamnose tol -rhamnulose, orl -fucose tol -fuculose was combined with a targeted phosphorylation reaction catalyzed byl -rhamnulose kinase (RhaB). The by-products (ATP and ADP) were selectively removed by silver nitrate precipitation method. In the second step, the phosphate group was hydrolyzed to producel -rhamnulose orl -fuculose with purity exceeding 99% in more than 80% yield (gram scale).